2002
DOI: 10.1007/s00216-002-1266-2
|View full text |Cite
|
Sign up to set email alerts
|

Sorptive sample preparation – a review

Abstract: Most sample-enrichment procedures currently available rely on adsorption of the analytes of interest by a suitable adsorbent material. Although good performance can be obtained for many practical problems, in some cases the applicability of adsorptive sample preparation falls short, particularly for the enrichment of polar and/or high-molecular-weight compounds, especially in combination with thermal desorption. Because of the very strong retention of adsorbent materials, undesired effects such as incomplete d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
194
0
17

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(212 citation statements)
references
References 98 publications
(139 reference statements)
1
194
0
17
Order By: Relevance
“…This ratio is equal to the ratio of the mass of the analyte in the extraction phase (m E ) over the mass of the analyte in the sample (m S ) times the phase ratio β, which is defined as the ratio between the volume of the sample (V S ) over the volume of the extraction phase (V E ) (27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This ratio is equal to the ratio of the mass of the analyte in the extraction phase (m E ) over the mass of the analyte in the sample (m S ) times the phase ratio β, which is defined as the ratio between the volume of the sample (V S ) over the volume of the extraction phase (V E ) (27).…”
Section: Resultsmentioning
confidence: 99%
“…Compound SPME/SBSE SPME SBSE SPME SBSE SPME SBSE SPME SBSE and the analyte, competitive interactions between analytes for adsorbent sites can occur, leading to lower reproducibility compared with pure sorbents (27). Several authors have reported higher reproducibility for PDMS coated stir-bar extractions compared with SPME extractions using copolymers for volatiles in water (28), vinegar (31) and malt whisky (32).…”
Section: Resultsmentioning
confidence: 99%
“…Microlitre amounts are injected for analysis. Sensitivity limitations are associated with injection of only a fraction of the final 20 µL to 1 mL solvent extract [26]. In contrast to extraction procedures using solvents, the procedure applied in this study is a novel solvent free sorptive extraction technique where DDT is concentrated from soil using polydimethylsiloxane (PDMS) loops.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to extraction procedures using solvents, the procedure applied in this study is a novel solvent free sorptive extraction technique where DDT is concentrated from soil using polydimethylsiloxane (PDMS) loops. PDMS functions as a hydrophobic solvent for the analytes [26]. After extraction the loop is inserted into a commercial thermal desorption tube for solventless introduction into a GC.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, VOCs analyses involve either static or dynamic headspace (HS) sampling, followed by gas chromatographic separation and flame ionization (GC-FID) or mass spectrometric detection (GC-MS). In the majority of the newly developed HS sample preparation techniques, the recovery of volatiles is based on sorption in a solid phase 8,9) . Among them, equilibrium sampling techniques such as HS solid-phase microextraction 10) , HS sorptive extraction 11,12) , and a non-equilibrium sampling technique, HS solid-phase dynamic extraction, are available 8) .…”
mentioning
confidence: 99%